The relationship between emotional intelligence and affective commitment: an examination of police officers - Baker, Rogis; Jaaffar, Amar Hisham; Sallehuddin, Hasimi; Hassan, Mohamed Ayyub; Mohamed, Rosmah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper examines the four dimensions of emotional intelligence: self-emotional appraisal (SEA), other's emotional appraisal (OEA), use of emotions (UOE) and regulation of emotions (ROE) in predicting effective commitment.The sample used for this study consisted of 372 police officers selected from five contingents: Kuala Lumpur, Selangor, Johor, Sabah and Sarawak. Testing our hypotheses in the field, we found strong evidence that the four dimensions of emotional intelligence: SEA, OEA, UOE and ROE enhance affective commitment. Additionally, the study provides evidence for the government to improve service quality and commitment to the police force.